Analysis of PAK Teacher Personality Competencies in Improving the Quality of Fair, Honest and Objective Learning - Samuel Moi Ganang Manik; Dorlan Naibaho (Journal of Cross Knowledge, 2024)
Teachers are the most prioritized component in the education system which must receive maximum attention. Apart from that, the personality competence of PAK teachers must also truly have a fair, honest and objective nature and be based on love, where the teacher plays a very important role in efforts to achieve the desired learning goals. As a Christian Religious Education teacher, you must maintain faith. belief by diligently worshiping, praying, and following in the footsteps of Jesus as a great teacher, where Christian Religious Education teachers do not only focus on teaching but are able to become caregivers and coaches, PAK teachers in conveying the gospel not only in the form of teaching but especially in terms of example. highlighted in their lives. Christian religious education teachers must also realize that they still have to continue learning and imitating Jesus Christ in teaching.